Delay in Seeking Institutional Delivery Services and Associated Factors Among Immediate Postpartum Mothers in Public Health Facilities in Gondar Town, Northwest Ethiopia, 2022 - Tazeb Alemu Anteneh; Zerfu Mulaw Endale; Getie Mihret Aragaw; Hana Yohanes Mamo; Betelhem Ketema; Temesgen Gashaw; Rahel Misaw; Tiringo Molla Tiruye (Women's Health Reports)
Background: Maternal and neonatal mortality is a global problem that is highly prevalent in low- and middle-income countries, including Ethiopia. Maternal delay in seeking institutional delivery services utilization plays a significant role in determining maternal and neonatal health outcomes. Although studies have been conducted on institutional delivery service utilization in Ethiopia, little is known about factors for delays in seeking care for institutional delivery services. Objective: This study aimed to assess the delay in seeking institutional delivery services and associated factors among immediate postpartum mothers in public health facilities in Gondar, northwest Ethiopia. Methods: A facility-based cross-sectional study was conducted from July 15 to September 10, 2022. A total of 391 participants were selected using systematic random sampling. Data were collected through face-to-face interviews using structured, pretested, and interviewer-administered questionnaires. Data were entered into EpiData version 4.6, and the analysis was conducted using Statistical Package for Social Science version 26. The multivariable logistic regression model was fitted and the level of significance was set at p ≤ 0.05. Result: The prevalence of delay in seeking institutional delivery was 49.10% (95% confidence interval [CI]: 44.13, 54.08). Rural residence (adjusted odds ratio [AOR] = 2.51; 95% CI: 1.43–4.41), no antenatal care visits (AOR: 2.87; 95% CI: 1.34–6.13), unplanned pregnancy (AOR: 2.98; 95% CI: 1.78–5.01), poor decision-making autonomy in maternity care services (AOR: 1.98; 95% CI: 1.15–3.40), and poor birth preparedness plan (AOR: 4.88; 95% CI: 2.79–8.53) were significantly associated with delays in seeking institutional delivery. Conclusion: Delays in seeking institutional delivery services were high. It is better to promote women’s decision-making power in their own health care. In addition, it is better to arrange programs that will improve maternal and child health service utilization.